Recent Approaches on Molecular Markers, Treatment and Novel Drug Delivery System Used for the Management of Colorectal Cancer: A Comprehensive Review - Chauhan, Sonia; Sharma, Sakshi (Current Pharmaceutical Biotechnology, 2024)
Colorectal cancer affects 1 in 25 females and 1 in 24 males, making it the third most frequent cancer with over 6,08,030 deaths worldwide, despite advancements in detection and treatments, including surgery, chemotherapeutics, radiotherapy, and immune therapeutics. Novel potential agents have increased survival in acute and chronic disease conditions, with a higher risk of side effects and cost. However, metastatic disease has an insignificant long-term diagnosis, and significant challenges remain due to last-stage diagnosis and treatment failure. Early detection, survival, and treatment efficacy are all improved by biomarkers. The advancement of cancer biomarkers' molecular pathology and genomics during the last three decades has improved therapy. Clinically useful prognostic biomarkers assist clinical judgment, for example, by predicting the success of EGFR-inhibiting antibodies in the presence of KRAS gene mutations. Few biomarkers are currently used in clinical settings, so further research is still needed. Nanocarriers, with materials like Carbon nanotubes and gold nanoparticles, provide targeted CRC drug delivery and diagnostics. Light-responsive drugs with gold and silica nanoparticles effectively target and destroy CRC cells. We evaluate the potential use of the long non-coding RNA (non-coding RNA) oncogene plasmacytoma variant translocation 1 (PVT1) as a diagnostic, prognostic, and therapeutic biomarker, along with the latest nanotech breakthroughs in CRC diagnosis and treatment.
Keywords: gene expression